Estimates for quality of life loss due to Respiratory Syncytial Virus - Hodgson, David (Influenza Other Respir Viruses, 2019)
BACKGROUND: In children aged <5 years in whom severe respiratory syncytial virus (RSV) episodes predominantly occur, there are currently no appropriate standardised instruments to estimate quality of life years (QALY) loss. OBJECTIVES: We estimated the age‐specific QALY loss due to RSV by developing a regression model which predicts the QALY loss without the use of standardised instruments. METHODS: We conducted a surveillance study which targeted confirmed RSV episodes in children aged <5 years (confirmed cases) and their household members who experienced symptoms of RSV during the same time (suspected cases). All participants were asked to complete questions regarding their health during the infection, with the suspected cases additionally providing health‐related quality of life (HR‐QoL) loss estimates by completing EQ‐5D‐3L‐Y or EQ‐5D‐3L instruments. We used the responses from the suspected cases to calibrate a regression model which estimates the HR‐QoL and QALY loss due to infection. FINDINGS: For confirmed RSV cases in children under 5 years of age who sought health care, our model predicted a QALY loss per RSV episode of 3.823 × 10(−3) (95% CI 0.492‐12.766 × 10(−3)), compared with 3.024 × 10(−3) (95% CI 0.329‐10.098 × 10(−3)) for under fives who did not seek health care. Quality of life years loss per episode was less for older children and adults, estimated as 1.950 × 10(−3) (0.185‐9.578 × 10(−3)) and 1.543 × 10(−3) (0.136‐6.406 × 10(−3)) for those who seek or do not seek health care, respectively. CONCLUSION: Evaluations of potential RSV vaccination programmes should consider their impact across the whole population, not just young child children.